Systematic review and meta-analysis on brucellosis seroprevalence in ruminants (1970 – 2020) of India - LALRINZUALA, MICHAEL V; R, VINODHKUMAR O; TAMTA, SHIKHA; SINGH, D K; LALSANGZUALA, C; KHAWASKAR, DAMINI; ROTLUANGKIMI; SINGH, B R; SINHA, D K (The Indian Journal of Animal Sciences, 2023)
Brucellosis is one of the most common contagious and neglected bacterial zoonotic diseases. The disease has been reported in ruminants in almost all Indian states. But there is a lack of comprehensive information on the seroprevalence of brucellosis in the Indian subcontinent. A systematic review and meta-analysis on the seroprevalence of brucellosis among ruminants of India was conducted from the published articles (January 1970 - June 2020) by including 172 studies screened from 567 publications. The estimated brucellosis seroprevalence of cattle, buffalo, sheep, goat, yak and mithun was 14% (95% CI: 12% - 16%), 8% (95% CI: 6% - 9%), 8% (95% CI: 7% - 10%), 8% (95% CI: 7% - 9%), 16% (95% CI: 7% - 28%) and 26% (95% CI: 12% - 42%), respectively. Sub-group analysis was performed based on diagnostic tests, regions, publication year, and sample size. The estimated seroprevalence of brucellosis in cattle and goats was found to be higher in the central region compared to other regions. Similarly, the western region showed a higher seroprevalence for brucellosis in buffalo and sheep. Given the estimated animal population of 2021, the meta-analysis estimated that the total number of seropositive animals would be 26.95 million cattle (95% CI: 23.09–30.78), 8.78 million buffaloes (95% CI: 6.59–9.89), 5.94 million sheep (95% CI: 5.20–7.43), 11.91 million goats (95% CI: 10.42–13.40), 9.6 thousand yaks (95% CI: 0.0042–0.0168), and 100 thousand mithun (95% CI: 0.05–0.16). Further, the comprehensive picture of the brucellosis seroprevalence may help the decisionmaking authorities in formulating better prevention and control strategies for brucellosis in India.